COPING STRATEGIES OF NURSES IN THE FACE OF WORKLOAD AND EMOTIONAL STRESS IN INTENSIVE CARE UNITS: A QUALITATIVE STUDY - Dewi, Rinawati; Budianto, Arya; Novitasari, Laeli (Jurnal Multidisipliner Bharasa, 2026)
Intensive care units are work environments that have a high level of complexity, high clinical risks, and demands for quick and accurate decision-making. This condition causes the nurses on duty in this unit to face heavy workloads and significant emotional stress. The pressure stems not only from the patient's critical condition, but also from interactions with patients' families, multidisciplinary team dynamics, and strict administrative and documentation demands. If not managed adaptively, this condition has the potential to cause work stress, emotional exhaustion, and even burnout which has an impact on the quality of service and patient safety. This study aims to explore in depth the coping strategies used by nurses in dealing with workload and emotional stress in intensive care units. The research uses a qualitative approach with a descriptive phenomenological design. Twelve nurses were selected by purposive sampling based on the criteria of at least two years of work experience in the intensive care unit. Data collection was carried out through semi-structured in-depth interviews and analyzed using thematic analysis. The results of the study identified five main themes, namely personal emotion regulation, social support from colleagues, strengthening spirituality, professional competency development, and time management strategies and work priorities. These findings show that nurse coping strategies are multidimensional and influenced by individual factors as well as the organizational environment. This study recommends strengthening organizational support and mental health promotive programs as part of nursing resource management in intensive care units.